AN ORIGINAL FOUR-PART STRATEGY TO INTRODUCE STUDENTS TO THE SOCIOLOGY OF FAMILY - Duffy, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Teaching strategies vary as widely as do personalities of Professors of Sociology across the planet. We each have our skills, our talents, our methods. What we share is subject matter, and whether it is a course devoted entirely to the Sociology of Family or is a one-day lesson devoted to Family Relationships within an Introduction to Sociology course, there are critical concepts to be presented to students that will immediately immerse them in the subject of Family. The purpose of this article, therefore, is to present four lessons a sociology professor could present to students to critically-assess the concept of Sociology of Family. When I say "I," consider "I" as yourself as Professor.